Association of Insulin Dose, Cardiometabolic Risk Factors, and Cardiovascular Disease in Type 1 Diabetes During 30 Years of Follow-up in the DCCT/EDIC Study - Braffett, Barbara H. (Diabetes Care, 2019)
OBJECTIVE: The Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) study demonstrated the beneficial effects of intensive therapy on atherosclerosis and clinical cardiovascular disease (CVD) outcomes. The current analyses evaluated the relationship between longitudinal changes in insulin dose and CVD risk factors and outcomes. RESEARCH DESIGN AND METHODS: A total of 1,441 participants were randomly assigned to intensive or conventional diabetes therapy during the DCCT. After an average of 6.5 years of follow-up, 96% of the surviving cohort enrolled in the EDIC observational study, which included annual visits with detailed medical history, physical examination, and laboratory testing. CVD events were adjudicated by a review committee. Generalized linear mixed models and Cox proportional hazards regression models were used to assess the association between insulin dose and cardiometabolic risk factors and CVD risk, respectively, over a total of 30 years. RESULTS: Higher insulin doses were significantly associated with a less favorable cardiometabolic risk profile (higher BMI, pulse rate, and triglycerides and lower HDL cholesterol) with the exception of lower diastolic blood pressure and lower LDL cholesterol. In a minimally adjusted model, a 0.1 unit/kg body wt/day increase in insulin dose was associated with a 6% increased risk of any CVD (95% CI 3, 9). However, the association with insulin dose was no longer significant after adjustment for other CVD risk factors. CONCLUSIONS: During DCCT/EDIC, higher insulin doses were associated with adverse trends in several cardiometabolic risk factors, even after multivariable adjustment, but not with incident CVD outcomes.